Perception and behavior of urban women regarding fertility: a cross sectional study - Kaushal, Suneel Kumar; Kaushal, Meenal; Prakash, Gyan; Misra, Sunil Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Fertility is only way for biological replacement of human being in order to continue its existence on earth. The fertility behavior of any population is influenced by various factors. Objective of the study is to study the fertility perception and behavior among urban women in Agra and understand the social factors on perception of women regarding fertility behavior among study group women. Methods: Community based, Cross-sectional study was done among 280 married women of reproductive age group residing in Agra City, using a standardized questionnaire to assess their fertility perception and behavior. Results: Mean age of marriage was 19.01 years. About 70% of women married before the age of 20. Mean gap between marriage and first child was 1.57 years. The mean least birth interval was 1.61 years. Less than one third of women desired for more than two children. Level of education, transition from lower to high SE status, significantly shifts the preferred family size. Conclusion: Majority of women considered appropriate age of marriage 18 year and above, gap between marriage and first child two years and above, wishes for two child norm. However, two third had confessed the necessity of mail child. Level of education and working status of women had positively effect.